Community well-being dimensions in Gunung Mulu National Park, Sarawak, Malaysian Borneo - Mohamad Syahrul Nizam Ibrahim; Shazali Johari; Mohamad Ibrani Shahrimin Adam Assim; Syamsul Herman Mohammad Afandi; Waseem Razzaq Khan; Suziana Hassan (Humanities & Social Sciences Communications, 2023)
Abstract The local communities living around national parks or areas like World Heritage Site (WHS) are crucial stakeholders to such settings. Their well-being needs to be unraveled so that the holistic management of the national park is in good condition to stabilize its status as WHS through the support and empowerment of the community. Numerous studies have been conducted on the biodiversity and geology of Gunung Mulu National Park (GMNP), but the community psychology aspect that is the foundation of conservation efforts has not been addressed. Therefore, this study aims to examine the community well-being dimensions in terms of environment, economics, social aspects as well as authority intervention based on the perspective of the local community and professionals with an emphasis on the current issues in GMNP. Quantitative and qualitative approaches were used in this study through a questionnaire to 99 local communities, and individual interviews that were conducted in GMNP and four nearby villages. Data were analyzed descriptively with four themes: environment; economics; social; and authority intervention. The findings showed that locals were satisfied in residing area in terms of environmental conditions. However, it does not reflect the actual situation, i.e., river water cloudiness, wildlife threat, degradation of wetlands, and solid waste issues are still happening. The constraints of the COVID-19 pandemic portrayed that they were very dissatisfied with their monthly income, which is very low compared to before. In terms of social, the services and facilities, especially treated water and electricity need improvement. It also noted that authority intervention especially related to road proposal, financial and skills assistance, and community conflicts could influence locals’ support for the planning and policies implemented in the national parks or WHS areas. This study suggests that relevant stakeholders should emphasize bottom-up approaches by considering aspects of community well-being that stem from multiple dimensions in order to achieve holistic national park management.